Análise do desempenho acústico de cômodos geminados: estudo de caso em um conjunto habitacional em Guarapuava-PR - Oliveira, Victória Assumpção de (2021)
The acoustic comfort of buildings has become a requirement of importance when evaluating a property. In the current pandemic scenario, this issue requires greater attention, as home office activities have intensified and the rooms in the employees' own residences served as workplaces, often not being appropriate for this function. At the same time, the vertical growth of cities is a reality, generating greater proximity to homes, which as a consequence increases the perception of noise, especially air noise. With the implementation of the Brazilian performance standard (NBR 15575) in 2013, the acoustic insulation of buildings became an item in which it has pre- established requirements that must be followed, with public bodies being responsible for such inspection. Therefore, this study aims to analyze the acoustic performance of a housing complex in the city of Guarapuava-PR, due to its growth in the civil construction sector. The measurements followed the engineering method carried out in the field covered by NBR 15575-4 (ABNT, 2021), in semi-detached, unfurnished and unoccupied rooms. Data on sound pressure level, reverberation time and background noise of the environments were collected, performing the energy averages of the results and the final analysis in R code. The results obtained, when compared with the normative requirements, showed that the berooms and living rooms in housing units need improvement to meet the standard, while kitchens and living rooms separated by the hall are classified as a minimum performance level. In summary, it is clear that the environmental comfort of users is still an aspect that needs better constructive analysis, as post-construction improvements present greater executive difficulty and, mainly, exposing users to excessive noise can cause serious health problems.